Development of DNA aptamers for visualization of glial brain tumors and detection of circulating tumor cells - Anna S. Kichkailo; Andrey A. Narodov; Maria A. Komarova; Tatiana N. Zamay; Galina S. Zamay; Olga S. Kolovskaya; Evgeniy E. Erakhtin; Yury E. Glazyrin; Dmitry V. Veprintsev; Roman V. Moryachkov; Vladimir V. Zabluda; Irina Shchugoreva; et al. (Elsevier, 2023)
Here, we present DNA aptamers capable of specific binding to glial tumor cells in vitro, ex vivo, and in vivo for visualization diagnostics of central nervous system tumors. We selected the aptamers binding specifically to the postoperative human glial primary tumors and not to the healthy brain cells and meningioma, using a modified process of systematic evolution of ligands by exponential enrichment to cells; sequenced and analyzed ssDNA pools using bioinformatic tools and identified the best aptamers by their binding abilities; determined three-dimensional structures of lead aptamers (Gli-55 and Gli-233) with small-angle X-ray scattering and molecular modeling; isolated and identified molecular target proteins of the aptamers by mass spectrometry; the potential binding sites of Gli-233 to the target protein and the role of post-translational modifications were verified by molecular dynamics simulations. The anti-glioma aptamers Gli-233 and Gli-55 were used to detect circulating tumor cells in liquid biopsies. These aptamers were used for in situ, ex vivo tissue staining, histopathological analyses, and fluorescence-guided tumor and PET/CT tumor visualization in mice with xenotransplanted human astrocytoma. The aptamers did not show in vivo toxicity in the preclinical animal study. This study demonstrates the potential applications of aptamers for precise diagnostics and fluorescence-guided surgery of brain tumors.